A round robin study on modelling the fire resistance of a loaded steel beam. (September 2017) - Lange, David; Boström, Lars
Abstract: This paper details a round robin study of the calculated response of structures in fire. In this instance, the study is based on one of two fire tests which were conducted on steel beams in a horizontal fire resistance furnace. The two specimens in the tests were identical having come from the same cast flow. The tests were conducted according to EN 1365-3 and the steel beams had a total length 5.4 m, spanning 5.2 m. These tests also formed a part of a testing round robin, reported elsewhere. The calculations were conducted by round robin participants in two stages. In the first instance a prediction of the response was made without knowledge of the measured temperatures of the steel beam and with only the grade of steel and details of the test setup. In the second instance the participants were also given the measured elastic limit of the steel, which differed significantly from the elastic limit implied by the grade, as well as measured temperatures from the steel beam and the plate thermometers from the furnace and asked to refine their model. Statistical analysis of the round robin results are presented to illustrate the variation which arises in the results of calculations. The results of the round robin study serve to illustrate the fire research and testing community's capability for modelling this simple case as well as the uncertainty in the calculation results. The results of the calculation round robin are also compared with the testing round robin to illustrate the comparative certainty between testing and calculations. Highlights: This paper details a round robin study of the calculated response of loaded steel beams in a fire resistance test. The calculations were conducted by round robin participants both before and after the test itself. Design tools or engineers have some variation which should be accounted for if using calculations for design / certification. No agreed failure criteria is a potential issue when calculations are relied upon for either certification or design.